Swedish National Election Study 2010 - Swedish election study 2010 - Holmberg, Sören; Ekengren Oscarsson, Henrik (University of Gothenburg, 2017)
This is the seventeenth election study carried out in Sweden in connection with a Swedish general election. Many of the questions are replications of questions asked in one or several of the previous surveys, but there are also a number of questions not asked before.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Detta är den sjuttonde riksomfattande studien i serien undersökningar kring partival, valdeltagande och opinionsbildning inom den svenska valmanskåren i samband med ett riksdagsval. Undersökningen ingår som steg två i panelen 2006-2010 och som steg ett i panelen 2010-2014. Ett stort antal av frågorna har ställts i en eller flera tidigare valundersökningar, vilket gör stora delar av studierna jämförbara över tid.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 2010
VU10
Keywords: voting intention; röstavsikt; trust; förtroende; voting; röstning; parliamentary elections; riksdagsval; political interest; politiskt intresse; party identification; partiidentifikation; election broadcasting; valbevakning i tv och radio; news; nyheter; foreign policy; utrikespolitik; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; party politics; partipolitik; political parties; politiska partier; political leaders; politiska ledare; election campaigns; valkampanjer; electoral issues; valfrågor; political attitudes; politiska åsikter; political issues; politiska frågor; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap